Engineering materials R. L. Timings. - Timings, R. L. (Roger Leslie), 1927- (Longman, 2000)
This is an updated edition of a two-part concise but comprehensive introduction to engineering materials for those more interested in the practical aspects of the subject than in the science and theory.